Relationships in couples treated with sperm donation - a national prospective follow-up study - Sydsjö, Gunilla (BioMed Central, 2014)
BACKGROUND: Long-term follow-up on relationship quality in couples who use sperm donation is scarce. Therefore, this study aimed to analyse changes over time in satisfaction with relationship in heterosexual couples who were scheduled for treatment with sperm donation and IVF couples treated with their own gametes and to compare the two groups undergoing different treatment for infertility. METHOD: A prospective follow-up study in which data were collected twice on two groups; couples receiving sperm donation and IVF couples using their own gametes. The ENRICH instrument was used to gain information about the individuals’ subjective experience of their relationship at the time of acceptance for treatment and again 2–5 years later. RESULTS: At the time of acceptance for treatment the men and women in the two groups assessed their relationships as being very solid on all dimensions and that there were no differences between the two groups. At the second assessment there was a decline in the satisfaction scores on the dimensions “Children and parenting” and “Egalitarian”, while an increase in scores was observed on “Conception of life” and “Conflict resolution” both for men and woman and also for the two groups. For the couples that had a successful treatment and gave birth to a child/children there was a decrease in satisfaction of the relation in the sperm donation group as well as in the group of couples having IVF with own gametes. CONCLUSION: In conclusion, the overall quality of relationship is stable in couples receiving donated sperm and does not differ from couples undergoing IVF-treatment with own gametes.